2010
DOI: 10.1007/s11355-010-0135-y
|View full text |Cite
|
Sign up to set email alerts
|

The concept of threshold and its potential application to landscape planning

Abstract: The concept of threshold can potentially be applied to conservation planning of species, habitats, and ecosystems. It also has significance in managing socialecological systems for resilience. However, our understanding and use of threshold has been scattered among various disciplines, and the link to conservation planning and social-ecological system management has not been strongly established. The review of the use of threshold in various disciplines reveals that the term is used in a similar manner in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Our results indicate a correlation between the proportion of impervious surfaces within a 500 m radius and the structure of bee assemblages in the Île‐de‐France region. In this context, determining a precise threshold for the proportion of impervious surfaces above which permanent changes occur in bee assemblages could greatly improve conservation measures for pollinating insects and plants within cities and should have implications for future urban landscape planning (Kato and Ahern ). As the world continues to change rapidly and becomes increasingly urbanized, new conservation policies are needed to preserve the ability of anthropized areas to provide habitats for pollinators.…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicate a correlation between the proportion of impervious surfaces within a 500 m radius and the structure of bee assemblages in the Île‐de‐France region. In this context, determining a precise threshold for the proportion of impervious surfaces above which permanent changes occur in bee assemblages could greatly improve conservation measures for pollinating insects and plants within cities and should have implications for future urban landscape planning (Kato and Ahern ). As the world continues to change rapidly and becomes increasingly urbanized, new conservation policies are needed to preserve the ability of anthropized areas to provide habitats for pollinators.…”
Section: Resultsmentioning
confidence: 99%
“…"Once-size-fits-all" benchmarking approaches tend to disregard the local conditions and diversity of environmental, economic and cultural drivers that affect individual production performance (von Wirén-Lehr, 2001;Nader et al, 2008;Huggins, 2008[cited in van Zeijl-Rozema et al, 2011; Kato et al, 2011). Decoupling the benchmarking process from these drivers presents the risk of setting non-practicable targets, discouraging farmers' adoption of the information for learning, and undermining trust in the whole sustainability exercise.…”
Section: The Need For "Local Tuning"mentioning
confidence: 99%
“…Several studies have proposed a non-linear relationship between PISA and water quality, and have found that water quality degradation was associated with higher PISA values [5], [24]. In addition, it has been concluded that the threshold PISA values at which point water quality degradation begins are a critical factor in this relationship analysis [25], where these thresholds may depend on regional conditions and their different stages of urban and industrial development [16]. For example, Kim et al (2016) found that PISA threshold values for several water quality indicators (including biological oxygen demand (BOD), permanganate index (CODMn), total organic carbon (TOC), and total phosphorus (TP)) was 9.80% for the Han River Basin of South Korea [24].…”
Section: Introductionmentioning
confidence: 97%